Study of Obstetric Admissions to the Intensive Care Unit at PNS Shifa - Nusrat Noor, Nusrat Noor (Journal of Rawalpindi Medical College, 2020)
Objectives: To investigate the indications, interventions and clinical outcomes of pregnant and newly delivered women admitted to the multidisciplinary intensive care unit. Study Design: Retrospective review / observational study. Setting and Duration: Critical care unit of Pakistan Navy Ship Shifa hospital Karachi from 1st August 2017 to 31st July 2018. Materials and Methods: This study was carried out in 13 bedded Intensive care units of PNS Shifa hospital Karachi, over a period of one year. All obstetrics admissions to ICU up to 42 days postpartum were included in the study, while those patients admitted after 42 days of delivery were excluded. Results: During the study period, 2688 women delivered and 66 obstetric patients were admitted to ICU, which was 7.5% of all ICU admission and it accounted for 2.4% of all deliveries. The most common indication for admission to ICU was hypertension disorders of pregnancy 45.4% followed by obstetric haemorrhage in 42.4% cases. 75% of the cases belonged to the age group of 21-35 years. The parity of 60% of patients was in the range of P2-P4. During the stay in ICU, 9% of patients were put on ventilator support, 40.9% had blood product transfusion, while 45% received antihypertensive and anticonvulsant therapy. Maternal mortality was 4.5%. Conclusion: Hypertensive disorder of pregnancy and obstetric hemorrhage were the main indications for admission to ICU. A multidisciplinary team approach and timely recognition of complications development can lead to a better maternal outcome. Universal availability of antenatal care can help in reducing serious complications and admissions to ICU.